2016
DOI: 10.1111/cts.12423
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Methylphenidate in Healthy Adults Emphasizing Novel and Known Effects of Several Carboxylesterase 1 (CES1) Variants

Abstract: The aim of this study was to identify demographic and genetic factors that significantly affect methylphenidate (MPH) pharmacokinetics (PK), and may help explain interindividual variability and further increase the safety of MPH. d‐MPH plasma concentrations, demographic covariates, and carboxylesterase 1 (CES1) genotypes were gathered from 122 healthy adults and analyzed using nonlinear mixed effects modeling. The structural model that best described the data was a two‐compartment disposition model with absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 43 publications
2
17
1
Order By: Relevance
“…Given that chemical structures differ significantly among enalapril, clopidogrel, and sacubitril, we speculate that the involvement of amino acid residues in catalyzing the cleavage of the ester bonds of these compounds may vary, which may have resulted in the observed substrate-dependent effect of the three nsSNPs. A recent healthy volunteer study reported that the area under the curve of D-methylphenidate plasma concentrations was increased by 68% in A269S carriers compared with noncarriers after subjects were administered a single dose of 10 mg methylphenidate (Lyauk et al, 2016). However, our in vitro studies of transfected cells and human livers showed that A269S was not associated with CES1 expression or activity.…”
Section: Discussioncontrasting
confidence: 62%
“…Given that chemical structures differ significantly among enalapril, clopidogrel, and sacubitril, we speculate that the involvement of amino acid residues in catalyzing the cleavage of the ester bonds of these compounds may vary, which may have resulted in the observed substrate-dependent effect of the three nsSNPs. A recent healthy volunteer study reported that the area under the curve of D-methylphenidate plasma concentrations was increased by 68% in A269S carriers compared with noncarriers after subjects were administered a single dose of 10 mg methylphenidate (Lyauk et al, 2016). However, our in vitro studies of transfected cells and human livers showed that A269S was not associated with CES1 expression or activity.…”
Section: Discussioncontrasting
confidence: 62%
“…Thus, one may hypothesise that one of these SNPs, or the combination of them, affects the metabolism of MPH. Of importance, two of the three individuals harbouring the intron 5 SNPs also harboured the rs115629050 (TG) SNP in exon 7, which, in a previous simulation‐based population pharmacokinetic study, was reported to increase the d ‐MPH AUC by 68% . Whether the observed effect was influenced or exerted by this exon 7 SNP or was due to the combination is unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Of importance, two of the three individuals harbouring the intron 5 SNPs also harboured the rs115629050 (TG) SNP in exon 7, which, in a previous simulation-based population pharmacokinetic study, was reported to increase the d-MPH AUC by 68%. 21 Whether the observed effect was influenced or exerted by this exon 7 SNP or was due to the combination is unknown. In a previous study, Yamada et al reported a minor allele frequency of 41.2% for these intron 5 SNPs in a mixed Canadian population, 22 which is considerably higher than the frequency of 4% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Another published study investigated the impact of carboxylesterase-1 enzyme and other covariates on the inter-subject variability for dand l-MPH following oral administration of ER Ritalin LA ® . This study used a 3-transit-compartment ER model in NONMEM to estimate population parameters [6]. The study was conducted in adult subjects using sparse and rich sampling.…”
Section: Introductionmentioning
confidence: 99%
“…The major problem with current published PK models is the inability of the mean data to adequately predict peak exposure [5][6][7] and measure true inter-subject variability. The purpose of this paper is to modify this physiological model and apply it to the PK of publicly-available individual subject parameters derived from fitted individual adult subject data [2,8].…”
Section: Introductionmentioning
confidence: 99%